Associations Between Cooking Fuel Exposure and Acute Respiratory Infection Symptoms in Children Under 5 Years - Areta, Diga; Haryanto, Budi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Acute Respiratory Infection (ARI) has emerged as a significant public health issue due to its status as the primary cause of illness and death among children under the age of 5. Methods: This study analyses the association between exposure of cooking fuel and risk factors for acute respiratory infection symptoms in children under 5 years of age. A cross-sectional approach using the 2017 Indonesia Demographic and Health Survey data. The data were analysed using logistic regression. Results: Results of the study show that among 5473 households, 26% of children under 5 years old experience symptoms of ARI. In the final result of the multivariate analysis, cooking fuel was not significantly associated with ARI. ARI was significantly associated with poor wealth index (aOR = 0,9; CI 95% = 0,73?1,01) and unimproved drinking water sources (aOR = 1,3; CI 95% =1,03-1,52). Conclusion: This study is expected to be a consideration for the government to immediately intervene for households with insufficient living habits and poor household sanitation. Also, increasing family awareness related to the risk of ARI in children under 5 years old.